2014
DOI: 10.18632/oncotarget.2633
|View full text |Cite
|
Sign up to set email alerts
|

LIGHT/TNFSF14 increases osteoclastogenesis and decreases osteoblastogenesis in multiple myeloma-bone disease

Abstract: LIGHT, a TNF superfamily member, is involved in T-cell homeostasis and erosive bone disease associated with rheumatoid arthritis. Herein, we investigated whether LIGHT has a role in Multiple Myeloma (MM)-bone disease. We found that LIGHT was overproduced by CD14+ monocytes, CD8+ T-cells and neutrophils of peripheral blood and bone marrow (BM) from MM-bone disease patients. We also found that LIGHT induced osteoclastogenesis and inhibited osteoblastogenesis. In cultures from healthy-donors, LIGHT induced osteoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 62 publications
7
57
1
3
Order By: Relevance
“…They release the receptor-binding domain into the extracellular space [39,40,42]. It has been recently reported that LIGHT inhibits osteoblastogenesis of MSC co-cultured with monocytes in multiple myeloma-bone disease [43]. There are possibilities that LIGHT signaling might be hampered by various cytokines or factors produced in the environment including soluble LIGHT, soluble HVEM, and its soluble receptor, DcR3.…”
Section: Discussionmentioning
confidence: 99%
“…They release the receptor-binding domain into the extracellular space [39,40,42]. It has been recently reported that LIGHT inhibits osteoblastogenesis of MSC co-cultured with monocytes in multiple myeloma-bone disease [43]. There are possibilities that LIGHT signaling might be hampered by various cytokines or factors produced in the environment including soluble LIGHT, soluble HVEM, and its soluble receptor, DcR3.…”
Section: Discussionmentioning
confidence: 99%
“…52 The description, functional evaluation and validation of this anti-LIGHT antibody opens up many possibilities to study the role of LIGHT and define its therapeutic potential in preclinical murine models of immunerelated diseases (transplantation, tumor immunity and autoimmune diseases), 17,18,26,53,54,55 as well as in other pathologies in which LIGHT has been implicated, such as pulmonary fibrosis subsequent to chronic lung inflammation and idiopathic pulmonary fibrosis diseases, 56,57 skin fibrosis 58 and bone destruction through osteoclastogenesis. 59 This tool offers advantages over the classical approaches of using LTbR.Ig recombinant fusion protein because LTbR.Ig blocks LTab/LTbR in addition to LIGHT/LTbR/HVEM. 51 Administration of anti-LIGHT antibody in the above-mentioned disease models may help to clarify the contribution of LIGHT/LTbR/HVEM to the overall disease protection observed when using LTbR.Ig fusion protein.…”
Section: Discussionmentioning
confidence: 99%
“…LIGHT (homologous to lymphotoxins exhibiting inducible expression and competing with herpes simplex virus glycoprotein D for herpesvirus entry mediator [HVEM], a receptor expressed by T lymphocytes) is elevated in conditions such as RA and multiple myeloma (110,111). In vitro, LIGHT has been reported to induce osteoclastogenesis in RANKL-dependent and –independent manners and indirectly inhibit osteoblastogenesis (110,111).…”
Section: Immune Cytokines and Bonementioning
confidence: 99%
“…In vitro, LIGHT has been reported to induce osteoclastogenesis in RANKL-dependent and –independent manners and indirectly inhibit osteoblastogenesis (110,111). …”
Section: Immune Cytokines and Bonementioning
confidence: 99%